Care provided by older adults in active cancer treatment to a spouse: A scoping review. Issue 6 (July 2022) - Donison, Valentina; Yang, Helen; Ayala, Ana Patricia; Wills, Aria; Alibhai, Shabbir M.H.; Puts, Martine
Abstract: Objectives: Older adults with cancer may be spousal caregivers for partners with one or more chronic conditions, and there has not been an overview of the needs of this population. Therefore, we conducted a scoping review to assess what is known about the type and amount of spousal care provided by older adults (≥65 years) with any type of cancer, in the active treatment phase. Materials and methods: A search strategy was designed with a Health Sciences Librarian and performed using the following electronic databases from inception to January 2021: Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica Database (Embase), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and PsycInfo. Two independent reviewers screened all abstracts and full-text studies for inclusion. Results: Searches were run February 26, 2020, and re-run January 8, 2021. A total of 8887 titles and abstracts were screened and 32 selected for full text review, but only two case reports were included in this review. The two case reports discussed the experience of an older adult with cancer, in active treatment, as the caregiver to a spouse. However, the type and amount of care provided by the caregiver to the spouse was not specified in either report. In both reports, caregivers declined cancer therapy to focus on the needs of the care recipients. Conclusion: Only two case reports were identified that examined the experiences of older adults with cancer acting as caregivers to a spouse. It is important for future studies to address this gap to better understand the needs of this population and develop future supportive interventions.